EFFECT OF ONLINE LEARNING MEDIA QUALITY ON STUDENT LEARNING EFFECTIVENESS AT SMPN 13 SUKABUMI CITY - Muttaqien, Ihsanul; Rachmawati, Ike; Purwanti, Dian (DIA: Jurnal Administrasi Publik, 2023)
This study aims to determine the effect of the quality of Online Learning Media on the effectiveness of Student Learning in SMPN 13 Sukabumi. This research has been carried out from November to December 2022. The method in this study is to use quantitative research methods with operationalvariable approach or the influence between the independent variable and the dependent variable. Sampling technique in this study is to use Proposive sampling. Instrument in this study used a closed questionnaire with likert scale form. Data analysis techniques used in this study validity test, reliability test, normality test, determination, regression, and hypothesis test F. The results found in this study that there is a significant influence between the independent variable is the quality of instructional Media with the effectiveness of Student Learning in SMPN 13 Sukabumi. The results of this calculation is to use the SPSS program which is presented as follows: Based on the results of the study showed that from the calculation data, it was concluded that the independent variables (X) simultaneously affect the dependent variable (Y). With the value of pegaruhnya between variables X and Y is equal to 36.3%, based on the value of R square. So according to the researcher that the independent variable (X) is the quality and dependent variable (Y) effectiveness there is a significant influence because of the variable X and variable Y.